REPRESENTATION OF SITA AND URMILA IN THE 21ST CENTURY: A STUDY OF SITA AND URMILA OF AMISH TRIPATHI’S SITA: THE WARRIOR OF MITHILA AND KAVITA KANE’S SITA’S SISTER - SREENI, AMULYA; VARSHA K, (International Journal of Psychosocial Rehabilitation, 2020)
Mythology is considered as vital entity in various religious cultures. Today Mythology is known and perceived by reader’s to various retellings . This paper focuses on the comparative study of the two mythical characters of Ramayana Sita and Urmila and how this characters has reshaped for the modern sensibility through comparative study. In the context of the character’s reviewed, for the comparative study of this two character’s feminism stands for the comparative study and interpretation. In Indian Mythology Women are showcased as weak can suppressed to male dominancy. The suppression is repeated as a cyclic process through the Women character’s the same trauma’s is showcased in Sita and Urmila in two unique characters of Ramayana has an overall different representation in Amish Tripathi and Kavita Kane